Analysis of DRM game control - Guo-jun MA; Qing-qi PEI; Xiao-hong JIANG (Tongxin xuebao)
To overcome the limitations of individual rationality,a game control model was proposed.The controller of game is global rational.To achieve global optimization,the controller chooses strategies according to the control goal,and the controlled chooses the strategies according to the principle of individual rationality.Based on the model and the analysis of relationships and actions of DRM value chain,a model of DRM game control is presented.Content provider actions as the controller of the game,and the global optimization strategies which the content provider choose are discussed,which provides the guidance theory of rational DRM applications.